2010
DOI: 10.1051/0004-6361/201014063
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking atomic data for astrophysics: Fe xi

Abstract: High-resolution spectroscopic observations of the solar corona and laboratory measurements are used to review all the line identifications for Fe xi, from the EUV to the visible. The results of the atomic structure and scattering calculations are presented elsewhere, while detailed comparisons between observed and predicted wavelengths and intensities are discussed here. All the brightest EUV lines in the solar corona are now finally firmly identified. Several new identifications are proposed, in particular, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…A few important temperature diagnostics for Hinode/EIS were discussed in Del Zanna (2009a,b and2010) and have not been repeated here. The various calibration problems for the Hinode/EIS instrument, highlighted here, will need to be properly assessed before these new temperature diagnostics can be used reliably.…”
Section: Discussionmentioning
confidence: 99%
“…A few important temperature diagnostics for Hinode/EIS were discussed in Del Zanna (2009a,b and2010) and have not been repeated here. The various calibration problems for the Hinode/EIS instrument, highlighted here, will need to be properly assessed before these new temperature diagnostics can be used reliably.…”
Section: Discussionmentioning
confidence: 99%
“…The previous identifications are due to Edlén (1937b) and Fawcett. The energies of the lower n = 3 levels have been carefully assessed in Del Zanna (2010) and are adopted here. Fig.…”
Section: Fe XImentioning
confidence: 99%
“…Keenan et al (2005) incorrectly identified the 2-39, 3-39 transitions with the lines observed at 189.19 and 189.72 Å respectively. (Del Zanna 2010) are shown, together with those obtained from our scattering target E target , those from our benchmark E bench , those from our benchmark including TEC E bench (TEC). We also list the values from the NIST compilation (E NIST ) and those calculated with the many-body perturbation theory (E MR−MP ) by Ishikawa & Vilkas (2008).…”
Section: Our Targetmentioning
confidence: 99%